Neottia linzhiensis (Orchidaceae, Epidendroideae, Neottieae), a new species from Xizang, China - Cai, Hong; Lin, Dong-Liang; Ye, Chao; Wang, Han-Chen; Yang, Bo-Yun; Jin, Xiao-Hua (Phytotaxa, 2023)
A new species of Orchidaceae, Neottia linzhiensis, from Motuo, Xizang, China, is described and illustrated. Neottia linzhiensis is similar to N. brevicaulis and N. taizanensis, but differs from them by having lip shallowly bilobed at apex, column not curve, and stigma nearly at column apex.